2020
DOI: 10.1002/ange.202003050
|View full text |Cite
|
Sign up to set email alerts
|

Diboran(4)azide als stabile Quelle für kurzlebige Iminoborane

Abstract: Wir berichten über die ersten isolierbaren, elektronen‐präzisen Diborane(4) mit Azidresten: das acyclische 1,2‐Diazido‐1,2‐bis(dimethylamino)diboran(4) und eine Reihe cyclischer 1,4‐Diaryl‐2,3‐diazido‐1,4‐diaza‐2,3‐diborine (Aryl=Mesityl, 2,6‐Xylyl, 4‐Tolyl). Im Gegensatz zu den kürzlich von uns beschriebenen kurzlebigen Diboran(4)aziden, welche sich bereits bei Raumtemperatur spontan zersetzen, erweisen sich die hier dargestellten Moleküle als thermisch äußerst robust. So können diese kontrollierte Pyrolysere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…This is primarily due to the fact that only a few stable azido diborane(4) compounds are known so far, such as compounds 6 and 7 reported by Braunschweig et al. (Figure 2b) [42] . Further attempts by Braunschweig et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily due to the fact that only a few stable azido diborane(4) compounds are known so far, such as compounds 6 and 7 reported by Braunschweig et al. (Figure 2b) [42] . Further attempts by Braunschweig et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the fact that only a few stable azido diborane(4) compounds are known so far, such as compounds 6 and 7 reported by Braunschweig et al (Figure 2b). [42] Further attempts by Braunschweig et al to synthesize diazido diboranes failed and demonstrated a relatively high instability of these compounds. [43] Recently, we reported the reaction of the ditriflato diborane [B(hpp)OTf] 2 (8) (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2α]pyrimidinate) [44] with nBu 4 NN 3 to give the diazido diborane [B(hpp)(N 3 )] 2 9 (see Lewis structure in Scheme 2).…”
Section: Introductionmentioning
confidence: 99%